Assessment of heavy metal pollution in soil and bottom sediment of Upper Egypt: comparison study - Abou El-Anwar, Esmat Ahmed (2021)
The average heavy metals content in the studied cultivated soils and Nile sediments are above the acceptable levels. Generally, Nile sediments and cultivated soils at Aswan and Luxor were unpolluted to moderately polluted with heavy metals. Pollution indices indicated that the studied Nile sediments were at considerably ecological risk from Cd (Er = 138.89) and Zn (Er = 140.52). In contrast, the cultivated soil was at very high ecological risk from Cd (Er = 295.24).